Maintenance System Analysis Using the Total Productive Maintenance (TPM) Method - Ananta, Yusril; Pradana, Bayu Ilham (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the maintenance system of the mill station at PG Krebet Baru Unit of PT PG Rajawali I, evaluate its effectiveness, and provide recommendations for improving machinery and production equipment maintenance based on the Total Productive Maintenance (TPM) method. Design/methodology/approach – This quantitative descriptive study uses observation, interviews, and document analysis. The data were analyzed using Overall Equipment Effectiveness (OEE), Six Big Losses analysis, and Fishbone Diagram to evaluate maintenance performance and identify production losses. Findings – The results show that maintenance activities are implemented through preventive, breakdown, and predictive approaches. The OEE value reached 98.53%, with availability at 99.17%, performance efficiency at 99.97%, and quality rate at 99.38%. The Six Big Losses analysis indicates that the largest loss is reduced speed losses at 6.9%. Originality/value – This study applies a TPM-based evaluation combining OEE and Six Big Losses analysis to identify efficiency issues in sugar milling operations, providing practical recommendations for improving maintenance performance and production stability..